2024
DOI: 10.1002/anie.202319712
|View full text |Cite
|
Sign up to set email alerts
|

The Photosalient Effect and Thermochromic Luminescence Based on o‐Carborane‐Assisted π‐Stacking in the Crystalline State

Kazuhiro Yuhara,
Kazuo Tanaka

Abstract: Herein, we report unique multiple‐stimuli responsiveness of anthracene‐tethered o‐carborane derivatives. We designed and synthesized anthracene derivatives with different substitution positions and numbers of the o‐carborane units. Two compounds had the characteristic crystal structure involving the columnar π‐stacking structures of the anthracene units. From the analysis of crystalline‐state structure‐property relationships, it was revealed that the crystals exhibit the photosalient effect accompanied with ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…Based on anthracene analogs, we aimed to clarify the structural factors which are required for the excimer formation. 42 As a result, we found that two structural features are essential. The first is that aromatic ring moieties need to stack and form a columnar structure.…”
Section: Photo-triggered Dimerization and The Photo-salient Effectmentioning
confidence: 84%
See 2 more Smart Citations
“…Based on anthracene analogs, we aimed to clarify the structural factors which are required for the excimer formation. 42 As a result, we found that two structural features are essential. The first is that aromatic ring moieties need to stack and form a columnar structure.…”
Section: Photo-triggered Dimerization and The Photo-salient Effectmentioning
confidence: 84%
“…In particular, it has recently been discovered that an o -carborane-modified anthracene derivative exhibits photo-triggered dimerization and a subsequent photosalient effect. 42 In this section, the mechanism is described.…”
Section: Photo-triggered Dimerization and The Photo-salient Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimuli-responsive luminescent materials show high prospects for applications in sensing and information security on account of the diverse and reversible changes in emission signals, such as intensity, color, and lifetime, , in correlation with environmental parameters. A variety of methods, including light, mechanical force, , temperature, water, , electricity, and chemicals, , have been used as the stimulation sources. As a basic physical parameter, temperature is one of the most common stimuli due to its accessibility, controllable range, and diverse application scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…38−45 For example, a geometry restricting the rotation of the aromatic group relative to the carborane cage in an ocarboranyl compound with a dimethylfluorene D group was shown to not only promote high-efficiency ICT-based emission but also enhance thermally activated delayed fluorescence. 34 Furthermore, compounds featuring o-carborane units linked to various π-aromatic fluorescent donors, such as naphthyl, 36,46,47 anthracenyl, 30,35,39,43,44,48 tetraphenylethenyl, 49,50 pyrenyl, 14,40,42 chrysenyl, 51 and indolocarbazole 52,53 moieties, can exhibit multiple photoluminescence and specific emissive features (e.g., mechanochromism, thermochromism, photosalient effect, etc.) in the TICT state.…”
Section: ■ Introductionmentioning
confidence: 99%